2003
DOI: 10.1046/j.1540-8175.2003.03021.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Noninvasive Reperfusion Criteria and Pulsed‐Wave Tissue Doppler Parameters in Patients With Acute Myocardial Infarction Receiving Thrombolytic Therapy

Abstract: Several studies have proven that noninvasive reperfusion criteria (NRC) have prognostic significance in patients receiving thrombolytic therapy (TT) after acute myocardial infarction (acute MI). In this study, we investigated the relationship between NRC and pulsed tissue Doppler (PTD) parameters in patients receiving TT after acute MI, and the role of PTD in the management and follow-up of patients with acute MI. The study group(n= 41)was divided into four subgroups defined as: anterior and posterior MI, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Thus, Sm obtained by TDI has been suggested to be an alternative method in recent years in the assessment of systolic myocardial functions of various cardiac diseases 6–13 . In the studies so far, it has been demonstrated that in mixed groups, there has been an agreement between Sm derived from PWD‐TDI or color M‐mode TDI and LVEF obtained by radionuclide or echocardiographic Simpson's method 6,13–18 . However, the correlation between Sm and LVEF has not been studied adequately in healthy subjects and in patients with HF separately.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Sm obtained by TDI has been suggested to be an alternative method in recent years in the assessment of systolic myocardial functions of various cardiac diseases 6–13 . In the studies so far, it has been demonstrated that in mixed groups, there has been an agreement between Sm derived from PWD‐TDI or color M‐mode TDI and LVEF obtained by radionuclide or echocardiographic Simpson's method 6,13–18 . However, the correlation between Sm and LVEF has not been studied adequately in healthy subjects and in patients with HF separately.…”
Section: Discussionmentioning
confidence: 99%
“…An agreement between Sm obtained by pulsed‐wave Doppler (PWD) or by color M‐mode TDI and LVEF obtained by various other methods has already been assessed in mixed groups, and the two parameters have been determined to agree with each other 6,13–18 . However, the agreement between Sm and LVEF has not been adequately studied in healthy subjects and those with heart failure (HF) separately.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Exact timing of DTI velocities in relation to the different phases of the cardiac cycle is possible by simultaneous recording of tissue velocities and ECG signals. Systolic time intervals measured by pulsed DTI had been used to evaluate regional left ventricular systolic dysfunction in patients with CAD 12 . However, the usefulness of mitral annulus systolic time intervals for the assessment of global left ventricular systolic function has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Systolic time intervals measured by pulsed DTI had been used to evaluate regional left ventricular systolic dysfunction in patients with CAD. 12 However, the usefulness of mitral annulus systolic time intervals for the assessment of global left ventricular systolic function has not yet been reported. In the present study, both PEP and TS at all the four mitral annular sites were significantly longer in the MI group than that in the control and the AP groups, while LVEF was significantly lower in the MI group compared with that in the control and the AP groups.…”
Section: First Reported Thatmentioning
confidence: 99%